DECIPHER pooled shRNA library screen identifies PP2A and FGFR signaling as potential therapeutic targets for diffuse intrinsic pontine gliomas. Issue 7 (3rd April 2019) - Schramm, Kathrin; Iskar, Murat; Statz, Britta; Jäger, Natalie; Haag, Daniel; Słabicki, Mikołaj; Pfister, Stefan M; Zapatka, Marc; Gronych, Jan; Jones, David T W; Lichter, Peter
Abstract: Background: Diffuse intrinsic pontine gliomas (DIPGs) are highly aggressive pediatric brain tumors that are characterized by a recurrent mutation (K27M) within the histone H3 encoding genes H3F3A and HIST1H3A/B/C . These mutations have been shown to induce a global reduction in the repressive histone modification H3K27me3, which together with widespread changes in DNA methylation patterns results in an extensive transcriptional reprogramming hampering the identification of single therapeutic targets based on a molecular rationale. Methods: We applied a large-scale gene knockdown approach using a pooled short hairpin (sh)RNA library in combination with next-generation sequencing in order to identify DIPG-specific vulnerabilities. The therapeutic potential of specific inhibitors of candidate targets was validated in a secondary drug screen. Results: We identified fibroblast growth factor receptor (FGFR) signaling and the serine/threonine protein phosphatase 2A (PP2A) as top depleted hits in patient-derived DIPG cell cultures and validated their lethal potential by FGF ligand depletion and genetic knockdown of the PP2A structural subunit PPP2R1A . Further, pharmacological inhibition of FGFR and PP2A signaling through ponatinib and LB-100 treatment, respectively, exhibited strong tumor-specific anti-proliferative and apoptotic activity in cultured DIPG cells. Conclusions: Our findings suggest FGFR and PP2A signaling as potential new therapeutic targets for the treatment of DIPGs.